2020
DOI: 10.1681/asn.2020020225
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Supplementation to Improve Vascular Stiffness in CKD: The K4Kidneys Randomized Controlled Trial

Abstract: BackgroundVascular calcification, a risk factor for cardiovascular disease, is common among patients with CKD and is an independent contributor to increased vascular stiffness and vascular risk in this patient group. Vitamin K is a cofactor for proteins involved in prevention of vascular calcification. Whether or not vitamin K supplementation could improve arterial stiffness in patients with CKD is unknown.MethodsTo determine if vitamin K supplementation might improve arterial stiffness in patients in CKD, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Since vitamin K deficiency represents a key feature in the development of VC, the effects of vitamin K substitution have been investigated. A recently published study comparing oral vitamin K2 substitution versus placebo in CKD patients showed no improvement in vascular stiffness or other measures of vascular health [139]. Vitamin K1 supplementation however is a promising and uncomplicated way to positively influence VC in CKD patients and, therefore, its effect on CV risk is under investigation in current clinical trials (Table 3) [135,140].…”
Section: Vascular Calcification In Ckdmentioning
confidence: 99%
“…Since vitamin K deficiency represents a key feature in the development of VC, the effects of vitamin K substitution have been investigated. A recently published study comparing oral vitamin K2 substitution versus placebo in CKD patients showed no improvement in vascular stiffness or other measures of vascular health [139]. Vitamin K1 supplementation however is a promising and uncomplicated way to positively influence VC in CKD patients and, therefore, its effect on CV risk is under investigation in current clinical trials (Table 3) [135,140].…”
Section: Vascular Calcification In Ckdmentioning
confidence: 99%
“…Moreover, warfarin treatment (a vitamin K antagonist) induced coronary artery disease and vulnerable plaques in mice and vitamin K administration reversed such VC progression, suggesting the role of vitamin K in VC development [ 178 ]. However, the association between vitamin K status and VC in clinical observations are inconclusive [ 179 , 180 , 181 ] and the recent K4Kidneys trial failed to confirm the beneficial role of vitamin K supplement in vascular health [ 182 ].…”
Section: Possible Therapeutic Strategiesmentioning
confidence: 99%
“…Among the variety of methods evaluated for the measurement of vascular stiffness, APWV has been proven to have the best reproducibility and outcome validation and is the recommended method to test vascular stiffness by major regulatory bodies [40]. Recent studies with vitamin K therapy and nutritional vitamin D supplements have shown that vascular stiffness as examined by the APWV is a difficult parameter to modulate [41, 42], and at present time, no directed therapy is available for reducing vascular stiffness. While in vitro and in vivo studies show that hydroxychloroquine has the potentials to positively impact endothelial dysfunction, vascular calcification and smooth muscle dysfunction are also important modifiers of the vascular stiffness in CKD that are unlikely to be affected by hydroxychloroquine.…”
Section: Discussionmentioning
confidence: 99%